Image analysis, methanogenic activity measurements, and molecular biological techniques to monitor granular sludge from an EGSB reactor fed with oleic acid - Pereira, M. A. (2003)
Morphological changes in anaerobic granular sludge fed with increasing loads of oleic acid were quantified by image analysis. The combination of this technique with data on the accumulation of adsorbed long chain fatty acid and with the molecular characterization of microbial community gave insight into the mechanisms of sludge disintegration, flotation and washout. It was found that the bacterial domain was more affected than the archaeal domain during this process. However, no acetoclastic activity and only a residual hydrogenotrophic activity were detected in the sludge at the end of the operation.